Research tool - Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2018)
Background: Research usually uses a representative sample to draw an inference, thus it requires a methodologically strong research process that is ascertained by its research tool or instrument. Conclusion: A good research uses a validated research tool.